2007
DOI: 10.1097/01.jto.0000263713.38826.8e
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Phase II Trial of Two Schedules of Docetaxel in Elderly or Poor Performance Status Patients with Advanced Non-small Cell Lung Cancer

Abstract: Weekly docetaxel is associated with less neutropenia and a trend toward improved survival in elderly or PS 2 patients. PS rather than age is the primary determinant of outcome in this population. Octogenarians benefited from weekly docetaxel. Future studies should separate elderly patients from PS 2 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…This incidence of grade 3 or 4 neutropenia could possible be due to the proper intervention, including delay of chemotherapy administration, dose modification and application of G-CSF for treating neutropenia. This incidence of neutropenia could be considered as acceptable toxicity, when compared with that for docetaxel monotherapy [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…This incidence of grade 3 or 4 neutropenia could possible be due to the proper intervention, including delay of chemotherapy administration, dose modification and application of G-CSF for treating neutropenia. This incidence of neutropenia could be considered as acceptable toxicity, when compared with that for docetaxel monotherapy [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…A weekly D schedule (24) was selected as a control regimen instead of the triweekly schedule widely used in our country to facilitate the interpretation of study results. In addition, a previous study comparing the two schedules of D for elderly patients with advanced NSCLC reported a trend toward longer survival using a weekly regimen (25).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, vinorelbine is safe for elderly patient, even in those with poor performance status (Camerini et al, 2010). Previously, another study with docetaxel in monotherapy, comparing weekly to 3-weekly administration, had also conclude that this treatment is effective and well tolerated in older patients, even with poor performance status (Lilenbaum et al, 2007). An international expert panel ruled in favour of the use of single-agent chemotherapy in the elderly cancer patient.…”
Section: Type Of Single-agent Chemotherapymentioning
confidence: 99%